Comparative Evaluation of Protease Extraction from Leaves of Syzygium polyanthum - Noorhafiza Yahya; Zatul Iffah Mohd Arshad; Siti Kholijah Abdul Mudalip; Siti Zubaidah Sulaiman; Rohaida Che Man; Shalyda Md Shaarani; Mohd Hairul Ab. Rahim (Indonesian Journal of Chemistry, 2019)
In this study, the comparison of four extraction methods for protease from the leaves of Syzygium polyanthum was evaluated. The methods include sodium phosphate buffer, 1-methyl-8-oxyquinolinium betaine (QB) solvent based extraction, hydrogen-bond acceptor (HBA) solvent based extraction and Trichloroacetic-acetone (TCA) precipitation. The effectiveness of these extraction methods was measured based on the specific activity demonstrated by the crude protease extracted in this experiment. The results indicated that QB solvent-based extraction method could extract the crude protease from the leaves of S. polyanthum with the highest specific activity of 10.204 ± 0.329 U/mg compared to other extraction methods.